An overview of biosimilars - Shanmugarajan, Dayanidhi (International Journal of Basic & Clinical Pharmacology, 2024)
The paradigm of pharmacological therapy in diseases is shifting from conventional small molecule drugs to biological drugs produced by living systems. Biological drugs have extensively ramified into therapies of various conditions such as autoimmune disorders, haematological conditions, cancers and others. Biological drugs are currently the diamond mine of the pharmaceutical drug market. Due to the enormous market value, other pharmaceutical companies are keen in producing and marketing generic versions of these innovator (reference) biologic companies, once the patents start to expire. These generic versions of the biological drugs are called as biosimilars. However, biosimilars are not exactly generics of the originator biological drugs like in the case of conventional small molecule drugs. Various controversies and perplexities exist in their production, approval, marketing, and prescription. The reason for the mere existence of biosimilars or generics drugs for that matter is their reduced cost with preserved clinical effectiveness. Biosimilar drugs are subject to rigorous scrutiny by a thorough comparative evaluation with the reference biological product for marketing approval. It is also equally important for the physicians and pharmacists to have a sound body of knowledge about biosimilar drugs to optimally avail the benefits offered by them. This review highlights how biosimilar drugs differ from the conventional drugs, their development process, issues, and challenges associated with their use.